Effect of repeat-sprint training in hypoxia on post-exercise interleukin-6 and F2-isoprostanes - Goods, P. S. R.; Dawson, B.; Landers, G. J.; Gore, C. J.; Croft, K. (European Journal of Sport Science, 2016)
This investigation examined the oxidative stress (F2-Isoprostane; F2-IsoP) and inflammatory (interleukin-6; IL-6) responses to repeat-sprint training in hypoxia (RSH). Ten trained male team sport athletes performed 3(sets)*9(repetitions)*5 s cycling sprints in simulated altitude (3000 m) and sea-level conditions. Mean and peak sprint power output (MPO and PPO) were recorded, and blood samples were collected pre-exercise, and again at 8 and 60 min post-exercise. Both MPO and PPO were significantly reduced in hypoxia (compared to sea-level) in the second (MPO: 855?±?89 vs. 739 ± 95 W, p = .006; PPO: 1024 ± 114 vs. 895 ± 112 W, p = .010) and third (MPO: 819 ± 105 vs. 686 ± 83 W, p = .008; PPO: 985 ± 125 vs. 834 ± 99 W, p = .008) sets, respectively. IL-6 was significantly increased from pre- to 1 h post-exercise in both hypoxia (0.7 ± 0.2 vs. 2.4 ± 1.4 pg/mL, p = .004) and sea-level conditions (0.7 ± 0.2 vs. 1.6 ± 0.3 pg/mL, p < .001), with a large effect (d = 0.80) suggesting higher IL-6 levels of post-hypoxia. F2-IsoP was significantly lower 1 h post-exercise in both the hypoxic (p = .005) and sea-level (p = .002) conditions, with no differences between trials. While hypoxia can impact on exercise intensity and may result in greater post-exercise inflammation, it appears to have little effect on oxidative stress. These results indicate that team sport organisations with ready access to hypoxic training facilities could confidently administer RSH without significantly increasing the post-exercise inflammatory or oxidative stress response.